10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
BACKGROUND: Chagas disease (CD) is caused by Trypanosoma cruzi Chagas (genus Trypanosoma, family Trypanosomatidae, order Kinetoplastida), that is widespread in Latin America. The main hosts are humans and other domestic mammals, including dogs and cats. Studies have identified the domestic dog as a sentinel animal in the epidemiology of the disease in endemic regions to predict the risk of infection in humans. The indirect immunofluorescence (IIF) test, which is very sensitive but has low specificity, has been mainly used. OBJECTIVES: The aim of this study was to evaluate the performance of the IIF test compared to a reference array of chimeric antigens as a gold standard for the diagnosis of chronic canine CD. METHODS: The study included 330 serum samples from dogs living in a non-endemic Amazonian area in the Brazilian state of Maranhão. These were subjected to anti-T. cruzi antibody detection, using IIF and the latent class analysis (LCA) as reference tests, since there was no gold standard. RESULTS: LCA classified 284 samples as T. cruzi-negative, while 46 samples were predicted to be positive for T. cruzi antibodies. Compared with LCA, IIF showed a sensitivity and specificity of 43.5% and 70.1%, respectively, and an overall accuracy of 66.4%, and a positive and negative likelihood ratio of 1.45 and 0.81, respectively. The analysis also showed an estimated diagnostic odds ratio value of 1.79 and a Cohen's κ coefficient of 0.08 between the results of IIF and LCA. CONCLUSIONS: The poor performance of IIF, particularly in terms of sensitivity, makes it unsuitable for use in both serologic screening and laboratory diagnosis of CD in dogs.